## 2. Simplify these expressions a 6ab + (-3x) + 2ab b. 12x + 4y + (-3x) c 6w + (-2y) + 3w d 4abc + (-9abc) + 10d

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

## Answers ( )

Answer:Step-by-step explanation:a 6ab + (-3x) + 2ab

we have 6ab + 2ab – 3x =

8ab – 3xb. 12x + 4y + (-3x)

we have 12x – 3x + 4y =

9x + 4yc 6w + (-2y) + 3w

we have 6w + 3w – 2y =

9w – 2yd 4abc + (-9abc) + 10dwe have 4 abc – 9abc + 10d =

– 5abc + 10dHere for you.